Antiperiodic Wavelets (Journal of Computational Mathematics, 1996)
In this paper, we construct the orthogonal wavelet basis in the space of antiperiodic functions by appealing the spline methods. Differing from other results in papers$^{[1,2,3,6,8]}$, here we derive the 3-scale equation, by using this equation we construct some basic functions, those functions can be used to construct different orthonormal basis in some spline function spaces.